Etyka w reklamie bankowej — zadanie (nie)możliwe do spełnienia? - Rutkowska-Tomaszewska, Edyta; Szymonik, Anita (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In the current post-crisis reality and financial market situation, in the face of a crisis of values, the need to return to ethics and restore seriously damaged confidence in financial institutions, including banks, is becoming an important and current problem. Paying attention to the specificity of the services offered by banks on the financial market, as well as the banks themselves, the authors of this study analyse bank advertisements covered by the study in terms of their compliance with ethical principles in the post-crisis reality for the period 2009-2019 from the perspective of interventions undertaken by a self-regulatory body such as the Advertising Ethics Committee and the competition and consumer authority such as the President of the Office of Competition and Consumer Protection, as well as from the perspective of trust in banks. The aim is to try to answer the following questions: can any advertising activity be in line with the principles of ethics? Is the ethics of the banking services market, in the bank’s contractual relations with the customer, especially the consumer, especially in bank advertising, necessary, and possible, also in the context of trust in them?
Keywords: ethics; bank advertising; bank service; unfair advertising; trust in banks; codes of ethics